Factors That Influence Incident Of Urine Incontinence after Performed Dower Catheter - M. Projo Angkasa; Ahmad Baequny; Sri Hidayati (Poltekkes Kemenkes Semarang, 2012)
This study was explanatory research with cross sectional. Sampling was taken at adult inpatient ward that consist of Jlamprang ward, sekar jagad, truntum, maternity room, and for patient post performing catheter who were control at surgical polyclinic RSU Bendan. Quota sampling method was used for a period one month (1 – 30 September 2011). There were 34 respondents, and the analysis was used Chi – square continued with logistic regression. Only three independent variable had correlation that were age (p= 0,045), gender (p= 0.039), and infection of urine tract (p= 0.024). The dominant variable was infection of urine tract that gave contribution 3.95 times causing urine incontinence. Researchers’recomendation for nursing is to give more attention on sterility when performing and caring patient who are attached dower catheter to minimalized occurence infection of urine tract.